Wartości prorodzinne w świadomości młodzieży słowackiej w procesie przemian (2006 – 2011 – 2016) - Štefaňak, Ondrej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The present sociological study has arised and remains in area of empirical sociology of morality that aims to describe and explain moral reality. Its main goal is a description of the process of changes of Slovakian youth’s family environment and their moral attitudes in the area of marriage and family life. The study is composed of four parts. The first part presents the main models of changes in current pro-family values or marital and family morality. The second presents changes in intrafamily relations; the third focuses on changes in styles of moral education, while the fourth – on changes in attitudes of young people in relation to selected marriage and family moral norms. The study is based on three empirical researches carried out in 2006, 2011 and 2016.